Gray Matter Differences Between Healthy and Depressed Adolescents: A Voxel-Based Morphometry Study - Shad, Mujeeb U. (Mary Ann Liebert, Inc., 2012)
BACKGROUND: Major depressive disorder (MDD) frequently begins during adolescence and is associated with significant morbidity and mortality. However, little is known about the neurobiology of adolescent depression. A better understanding of the neurobiology will be helpful in developing more effective preventive and treatment interventions for this highly disabling illness. METHODS: Using a voxel-based morphometric method, the study compared gray matter and white matter volumes in 22 adolescents with MDD and 22 age- and gender-matched normal controls. RESULTS: Compared with controls, depressed adolescents had smaller gray matter volume in the frontal lobe and caudate nucleus bilaterally and right superior and middle temporal gyri. However, the groups did not differ significantly on white matter volume. CONCLUSIONS: These findings in depressed adolescents are consistent with the previous findings of gray matter abnormalities in frontolimbic areas and the striatum in depressed adults and suggest the presence of these structural changes at the onset of depressive illness.